A Virtual Dressing Room for People with Asperger’s Syndrome: A Usability Study to Realise Design Goals - Christiansen, Line Gad; Brooks, Anthony Lewis; Petersson Brooks, Eva; Rosenørn, Torben (Universal Access in Human-Computer Interaction. Design for All and Accessibility Practice, 2014)
Using the Virtual Dressing Room(VDR) system, which is created as a research project between different companies and universities in Denmark and funded by the Danish National Advanced Technology Foundation, a usability study has been conducted with people with Asperger’s Syndrome (AS), the initial aim was to determine if the people with AS would use the VDR system and understood it, as a second aim, the findings was used to determine a set of design goals. Seven teenagers with AS participated in the study, in the age range from 15 to 17 years old. A questionnaire was used before the study, to determine the target groups interests and how/if they purchase clothes. Through observations and video recording of the usability study, a qualitative interaction analysis provided a set of design goals to be used when designing for this target group. The goals emphasized the importance of an easy accessible and consistent solution with a limited amount of options and the importance of the user’s own preferences.